Maintaining Mental Health through the Role of Self-Compassion for Adolescents in Orphanages - Akbar Nur Aziz; Azam Syukur Rahmatullah (Universitas Negeri Surabaya, 2023)
The purpose of this study was to analyze the role of Self-Compassion on adolescent mental health in orphanages and analyze the causative factors and ways to overcome mental health disorders for adolescents in orphanages. The research method uses a mix method. Study 1 is quantitative data obtained from filling out questionnaires with a Likert scale with 43 samples aged 12-18 years. Quantitative data analysis using multiple linear regression. Study 2 is qualitative data obtained by conducting interviews, observations at the orphanage Minggir area, Sleman Special Region of Yogyakarta. Qualitative data analysis uses reduction techniques, display and conclusion drawing, as well. The results showed that: Study 1, there was an effect of Self-Compassion of 21.9% on the mental health of orphanage adolescents. The other 78.1% are other influences such as parenting, environment, self-openness, education, and so on. Study 2, Factors causing mental health disorders of orphanage adolescents include the background of adolescents from families of victims of domestic violence, victims of pornographic action and parenting that is not optimal. The implication of this study is that to improve mental health, it is necessary to instill a consistent self-compassion attitude for orphanage adolescents. ABSTRAK Tujuan penelitian ini adalah untuk menganalisis peran Self-Compassion terhadap kesehatan mental remaja di panti asuhan dan menganalisis faktor penyebab serta cara menanggulangi gangguan kesehatan mental bagi remaja di panti asuhan. Metode penelitian menggunakan mix method. Study 1 yakni data kuantitatif diperoleh dari pengisian kuesioner dengan skala likert dengan 43 sampel usia 12-18 tahun. analisis data kuantitatif menggunakan regresi linear berganda. Study 2 yakni data kualitatif diperoleh dengan melakukan wawancara, observasi di panti asuhan daerah Minggir, Sleman Daerah Istimewa Yogyakarta. Analisis data kualitatif menggunakan teknik reduksi, display dan penarikan kesimpulan, serta. Hasil penelitian menunjukkan bahwa: Study 1, terdapat pengaruh Self-Compassion sebesar 21.9% terhadap kesehatan mental remaja panti asuhan. 78.1% lainnya merupakan pengaruh lain seperti pola asuh, lingkungan, keterbukaan diri, pendidikan, dan sebagainya. Study 2, Faktor penyebab gangguan kesehatan mental remaja panti asuhan di antara lain ialah latar belakang remaja dari keluarga korban KDRT, korban porno aksi dan parenting yang tidak maksimal. Implikasi penelitian ini adalah guna meningkatkan kesehatan mental diperlukan penanaman sikap self-compassion yang konsisten bagi remaja panti asuhan.